HIV‐associated neurocognitive impairment in stable people living with HIV on ART in rural Tanzania. Issue 2 (15th November 2020) - Sanmartí, M; Meyer, AC; Jaen, A; Robertson, K; Tan, N; Mapesi, H; Samson, L; Ndaki, R; Battegay, M; Tanner, M; Weisser, M; Dalmau, D; et al.
Abstract : Objectives: Few studies have assessed cognitive impairment among healthy people living with HIV (PLWH) who are stable on antiretroviral treatment (ART) in sub‐Saharan Africa. Methods: We conducted a cross‐sectional study among a random sample of stable adult PLWH from rural Tanzania on ART for more than 1 year and without immunological failure or pre‐existing neurological disease. We evaluated the prevalence and risk factors for neurocognitive impairment (NCI), assessed through neuropsychological tests, functional and depression questionnaires and defined as a mean Z ‐score ≤ −1 in two or more cognitive domains. Results: Among 243 participants [median age = 44.3 years (interquartile range: 36–52] and 71% female] we found a rate of NCI of 19.3% (95% confidence interval: 14.8–24.8%). Memory and psychomotor domains demonstrated the highest impairment. Independent predictors of NCI were age and self‐reported alcohol use. Other classical risk factors were not associated with HIV‐associated NCI. Conclusion: Despite effective ART roll‐out, NCI remained a prevalent condition in this healthy rural Tanzanian population of PLWH on ART. Age and alcohol use were key risk factors.